Effect of muscle pre-activation properties on the magnitude of joint torque during voluntary isometric knee extension - Kim, J.-A.; Shin, N.; Lee, S.; Xu, D.; Park, J. (Korean Journal of Sport Biomechanics, 2021)
Objective: The purpose of this study is to identify the mechanism of changes in maximum voluntary torque with the magnitude and duration of pre-activation torque during voluntary isometric knee extension. Method: 11 male subjects (age: 25.91±2.43 yrs., height: 173.12±3.51 cm, weight: 76.45±7.74 kg) participated in this study. The subjects were required to produce maximal voluntary isometric torque with a particular pre-activation torque condition. The properties of pre-activation torque consisted of the combinations of 1) three levels of magnitude, e.g., 32 Nm, 64 Nm, 96 Nm, and 2) two levels of duration, e.g., 1 sec, and 3 sec; thus, a total of six conditions were given to the subjects. The force and EMG data were measured using the force transducers and wireless EMG sensor, respectively. Results: The results showed that the maximum voluntary torque increased the most with relatively large and fast (96 Nm, 1 sec) pre-activation condition. Similarly, with relatively large and fast (96 Nm, 1 sec) preactivation, it was found that the integrated EMG (iEMG) of the agonist muscles increased, while no significant changes in the co-contraction of the antagonist muscles for the knee extension. Also, the effect of pre-activation conditions on the rate of torque development was not statistically significant. Conclusion: The current findings suggest that relatively larger in magnitude and shorter in duration as the properties of pre-activation lead to a larger magnitude of maximal voluntary torque, possibly due to the increased activity of the agonist muscles during knee extension.